2015
DOI: 10.1016/j.parkreldis.2015.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Tremor-related quality of life: A comparison of essential tremor vs. Parkinson's disease patients

Abstract: Background Tremor-related quality of life is a multi-dimensional concept that reflects the physical, emotional and other health effects of tremor. Curiously, tremor-related quality of life has never been directly compared in patients with the two major tremor disorders, essential tremor (ET) and Parkinson’s disease (PD). We performed a head-to-head comparison of ET with PD patients. Methods The Quality of Life in Essential Tremor (QUEST) questionnaire was administered to 103 ET and 103 matched PD patients en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 27 publications
1
88
0
2
Order By: Relevance
“…The psychometric attributes of QUEST in ET patients have been assessed and most are satisfactory [9]. The psychometric attributes of QUEST have also been assessed in PD and are satisfactory [18]. …”
Section: Methodsmentioning
confidence: 99%
“…The psychometric attributes of QUEST in ET patients have been assessed and most are satisfactory [9]. The psychometric attributes of QUEST have also been assessed in PD and are satisfactory [18]. …”
Section: Methodsmentioning
confidence: 99%
“…It has also been found that ability to perform at work, and during leisure activity, impacts upon levels of depression for individuals with essential tremor [13]. As a result of the overlap in essential tremor and Parkinson's disease, previous research has not only explored the relationship between the two conditions [14] but has also compared quality of life [15]. In particular this comparison identified that individuals with essential tremor experienced more impairment in relation to writing, eating, drinking, embarrassment, and concentration [15] in comparison to individuals with Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the overlap in essential tremor and Parkinson's disease, previous research has not only explored the relationship between the two conditions [14] but has also compared quality of life [15]. In particular this comparison identified that individuals with essential tremor experienced more impairment in relation to writing, eating, drinking, embarrassment, and concentration [15] in comparison to individuals with Parkinson's disease. In addition, individuals with essential tremor were also found to have higher self-ratings of tremor severity in their arms, and drink alcohol more frequently than they would like, compared to individuals with Parkinson's disease, whereas the latter were noted to have higher levels of speech impairment and higher self-ratings of tremor severity in their legs compared to individuals with essential tremor [15].…”
Section: Introductionmentioning
confidence: 99%
“…Essential tremor (ET) is a progressive neurological disease that is associated with functional disability (1) and diminished quality of life (2). In addition to tremors, individuals with ET may have other motor and non-motor symptoms (3) including poorer balance (4, 5), cognitive impairment (6, 7), depression (8), and sleep dysregulation (9).…”
Section: Introductionmentioning
confidence: 99%